Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/bdra.20729
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal growth restriction and gene expression changes in a mouse model of fetal alcohol syndrome

Abstract: Growth restriction, craniofacial dysmorphology, and central nervous system defects are the main diagnostic features of fetal alcohol syndrome. Studies in humans and mice have reported that the growth restriction can be prenatal or postnatal, but the underlying mechanisms remain unknown.We recently described a mouse model of moderate gestational ethanol exposure that produces measurable phenotypes in line with fetal alcohol syndrome (e.g., craniofacial changes and growth restriction in adolescent mice). In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…Bcl11b encodes for a transcription factor with roles in embryonic tooth development (Katsuragi et al, 2013) and the development of T lymphocytes (Wakabayashi et al, 2003). It was not identified to be differentially expressed in any of the other tissues previously assayed in this ethanol model (Kaminen-Ahola et al, 2010a;Marjonen et al, 2015;Zhang et al, 2015), nor has it been identified in association with other models of prenatal ethanol exposure. Consequently, the differential expression of Bcl11b following ethanol exposure has not been further characterised in this project.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Bcl11b encodes for a transcription factor with roles in embryonic tooth development (Katsuragi et al, 2013) and the development of T lymphocytes (Wakabayashi et al, 2003). It was not identified to be differentially expressed in any of the other tissues previously assayed in this ethanol model (Kaminen-Ahola et al, 2010a;Marjonen et al, 2015;Zhang et al, 2015), nor has it been identified in association with other models of prenatal ethanol exposure. Consequently, the differential expression of Bcl11b following ethanol exposure has not been further characterised in this project.…”
Section: Discussionmentioning
confidence: 88%
“…These findings, while perhaps unsurprising given the absence of any apparent phenotype at 9.5 dpc, are seemingly at odds with those using the same ethanol model that identified numerous phenotypic outcomes and changes in the expression of various mRNAs and miRNAs in the adolescent and adult offspring (Kaminen-Ahola et al, 2010a;Marjonen et al, 2015;Zhang et al, 2015). Slc17a6 is one of the genes previously identified to be differentially expressed in the adult male hippocampus in the ethanol model .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations